PHYTOPLANKTON DIVERSITY IN THE WATERS OF LAKE SIBILI PALU CITY CENTRAL SULAWESI - Miswan Miswan; Sicilia Intan Safitri Ranga; Muhammad Fajri Ramadhan Muslim Shaleh; Umrah Umrah (Biocelebes, 2022)
The study "Phytoplankton diversity in the waters of Lake Sibili, Palu City, Central Sulawesi" was conducted in September 2021. This study aims to determine phytoplankton diversity in Lake Sibili, Tawaeli District, Palu City, Central Sulawesi. This study uses a method (purposive random sampling). The identification results obtained ten phytoplankton species, namely Bacillaria sp., Schroedeia pointera, Zygnemopsis circumcarinatum, Spirogyra plorifica, Shroedeia anchora, Biddulphia sp., Actinastrum gracillimum, Nitzschia actinastroides, Pleurotaenium nageli, and Schaeroplea annulina. Phytoplankton diversity index from each observation station with a diversity index value (station I) 1,726, (station II) 1,801, (station III) 1,743, (station IV) 1,647 and (station V) 1,728. Based on this, the level of phytoplankton diversity in Lake Sibili, Tawaeli District, Palu City, Central Sulawesi is classified as medium.